Permeability evolution of fluid-injection-reactivated granite fractures of contrasting roughnesses - Fengshou Zhang; Guanpeng He; Mengke An; Rui Huang; Derek Elsworth (Underground Space)
Fracture/fault instability induced by fluid injection in deep geothermal reservoirs could not only vary the reservoir permeability but also trigger hazardous seismicity. To address this, we conducted triaxial shear experiments on granite fractures with different architected roughnesses reactivated under fluid injection, to investigate the controls on permeability evolution linked to reactivation. Our results indicate that the fracture roughness and injection strategies are two main factors affecting permeability evolution. For fractures with different roughnesses, a rougher fracture leads to a lower peak reactivated permeability (kmax), and varying the fluid injection strategy (including the confining pressure and injection rate) has a less impact on kmax, indicating that the evolution of permeability during fluid pressurization is likely to be determined by the fracture roughness along the shear direction. Both the fracture roughness and injection strategies affect the average rates of permeability change and this parameter also reflects the long-term reservoir recovery. Our results have important implications for understanding the permeability evolution and the injection-induced fracture/fault slips in granite reservoirs during the deep geothermal energy extraction.